The Effectiveness of Wordwall Interactive Media in Teaching Mathematics in Elementary School: A Systematic Literature Review - Mirna Dewi; Berta Apriza; Karsoni Berta Dinata (Universitas Pendidikan Ganesha, 2025)
The low mathematics learning outcomes in elementary schools remain a significant issue in education, often caused by the lack of engaging and effective instructional media that can enhance students' interest and understanding. The use of interactive digital media such as Wordwall is believed to offer an innovative alternative for improving learning quality. This study aims to analyze the effectiveness of Wordwall as an interactive learning medium in enhancing elementary school students' mathematics learning outcomes and to evaluate the factors influencing its success. A systematic literature review (SLR) method was employed by examining 2,530 articles obtained through Google Scholar within the 2020–2024 period, which were narrowed down to 10 primary articles for in-depth analysis. Thematic analysis was used to identify relevant findings and patterns. The results indicate that Wordwall significantly improves students' mathematics learning outcomes, simplifies abstract concepts, and encourages active student participation through engaging learning activities. The successful implementation of this media is influenced by teachers' skills in designing Wordwall-based learning activities, students' engagement levels, and the integration of the media into various instructional strategies. This study concludes by recommending Wordwall as an effective technology-based interactive learning medium to improve mathematics learning outcomes in elementary education, while emphasizing the importance of instructional design, teachers’ digital competencies, and students' characteristics.